Thermal Stratification Effects on Electromagnetic Ferrofluid Flow over an Unsteady Stretching Sheet - Loganayagi, V.; Kameswaran, Peri K.; Hemalatha, K. (Discontinuity, Nonlinearity, and Complexity, 2026)
The concern of the present article is to look at the impacts of thermal stratification and heat transfer on two dimensional, laminar, incompressible nanofluid flow over an unsteady stretching sheet. The influence of thermal stratification added to the energy equation and temperature boundary condition. The nanoparticles sorted out here are Barium, and Zinc Ferrite. The base liquid as taken as water. The governing system of equations is reduced in the system of nonlinear differential equations and solved numerically. The influence of the thermal stratification parameter, electric field parameter on temperature, skin-friction, heat transfer rates has examined. The comparison made with the available outcomes in the literature and present outcomes is adequate concurrence with the literature’s findings for different estimations. A bit of the results shows that with an increase in thermal stratification parameter temperature profile decreases; subsequently, heat transfer rate increases. We also conclude an increase in the nanoparticle volume fraction that the heat transfer rate increases from Barium to Zinc ferrite.